Training on Making Black Soldier Fly Lure Media at the Nunnapa Freshwater Fish Farming Group: Pelatihan Pembuatan Media Pemikat Lalat Tentara Hitam Di Kelompok Budidaya Ikan Air Tawar Nunnapa - Maria Marselina Bay; Gonsianus Pakaenoni; Yolanda Getrudis Naisumu; Remigius Binsasi; Paskalis Abi (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
One of the freshwater fish farming groups in Kota Kefamenanu District is the Nunnapa Group. This group develops freshwater fish farming of tilapia and catfish. This group experiences business constraints in the form of low levels of knowledge and mastery of fish feed technology while the price of fish feed is high. On the other hand, insects have been studied as a source of protein, their use is recommended because they are more economical and environmentally friendly. The type of insect developed as an alternative feed with characteristics and abundant nutrient content is Hermetia illucens or black soldier fly (BSF) from the order Diptera, family Stratiomydae. This community service activity is aimed at increasing knowledge and mastery of feed technology in partners. This activity is expected to help fish farmers in Timor Tengah Utara (TTU) Regency, especially the Nunnapa fish farming group, to be able to produce alternative feed. The activity began with a survey, interviews, and socialization. Counseling and training on making female BSF fly lure media were carried out at the implementation stage. This lure media is expected to attract female BSF flies to come and lay eggs. The eggs that hatch into larvae (maggots) can be used as food for freshwater fish. The results of this service are expected to increase the production of freshwater fish, which in turn increases the income of partners and the welfare of the surrounding community in general.